GE_GERICHTE DCSO/488/2024 vom 17. Oktober 2024 - GE Cour de justice (2024)
Résumé: Recours interjeté au TF par la créancière le 31.10.2024 (5A_742/2024), rejeté par arrêt du 14 avril 2025 (5A_742/2024).